Enhancing the resilience of children and adolescents through drama pedagogy in times of crisis - Philippopoulou-Iosifidou, Maria; Mastrothanasis, Konstantinos (Education & Theatre, 2025)
The use of drama pedagogy has emerged as a significant method of supporting the psychosocial resilience of children and adolescents during times of crisis, such as pandemics, social upheaval and natural disasters. A key focus of this approach is addressing the negative impact of such crises on young people’s mental health and social development. Typical manifestations include anxiety, depression and social isolation. Using theatre and drama techniques has been shown to be an effective way of enhancing adaptive skills, promoting collectivity and fostering emotional well-being. This paper constitutes a theoretical study based on a narrative review of the international literature published between 2004 and 2024. It highlights the need for a long-term evaluation of theatre/drama-based interventions, as well as the importance of designing applications that are culturally and socially responsive. Drama pedagogy can reinforce psychological resilience and foster young people’s social and emotional competencies during times of crisis.